The Grand Old Duke of York;: Present-Day and Future Canadian Geoscience Education and Labour Market Trends - Raeside, Rob; Kosters, Elisabeth (Geoscience Canada, 2012)
SUMMARY The job market for Canadian earth scientists is significantly driven by the country’s strong resource industry. Enrolment in earth science degree programs is growing, but the demand from the job market is expected to outpace the projected supply from domestic programs. If the job market will indeed need as many workers as predicted, it will be necessary to change tactics for recruitment into Canadian university geosciences programs, to provide the market with the necessary workers.